The impact of incidental learning on the acquisition of the sound /p/ by Arabic-speaking EFL learners - Abdel Rahman Mitib Altakhaineh; Mohammad Yousef Alsaraireh; Hiba Alhendi (ExELL (Explorations in English Language and Linguistics))
The effect of incidental learning on acquiring the pronunciation of the phoneme /p/ by Arabic-speaking English as foreign language learners was the focus of this study. This phoneme was chosen because it does not exist in the phonemic inventory of Arabic. Eighth graders studying at Al-Ethra’a Secondary School in Alkarak were tested on the pronunciation of words containing /p/ in context (pretest). For three weeks, they were taught the primary stress of English words containing the target phoneme in their first or second syllable (treatment/incidental learning). The learning exercises consisted of explaining the stress rules and listening to native speakers uttering the words, followed by the participants’ repetition. The students were then re-tested (post-test) to determine whether incidental learning had affected the participants’ pronunciation of /p/. The results reveal that the treatment (incidental learning of /p/) had a positive impact on the participants' answers on the post-test.